Segregation and Recombination of Solanum Brevidens Synteny Groups in Progeny of Somatic Hybrids with S. Tuberosum: Intragenomic Equals or Exceeds Intergenomic Recombination - McGrath, J. M. (1996)
The Solanum brevidens genome (2n = 2x = 24) was examined with randomly applied polymorphic DNA (RAPD) markers in a second backcross population derived from a S. brevidens + S. tuberosum somatic hybrid. RAPD markers cosegregated into 12 different S. brevidens synteny groups. Most synteny groups were nonrecombinant. However, nearly 40% of the S. brevidens synteny groups detected in this population were recombinant deletions that carried at least one, but not all, synteny group-specific RAPD markers. All S. brevidens synteny groups (except chromosome 5) were involved in recombination, and recombination occurred within most intervals between markers. About 20% of the recombinant S. brevidens synteny groups involved a single synteny group-specific marker. The inheritance of some single-marker representatives was followed in four BC(3) families. At least nine changes in S. brevidens synteny groups had occurred during backcrossing. Six of the nine changes involved translocation of S. brevidens markers between nonhomologous S. brevidens chromosomes, and three S. brevidens markers may have been introgressed into the potato genome.